Avaliação de unitizadores para entregas de remessas na meia milha: fatores condicionantes para determinação do contenedor - Antezana, Gerardo Herrera (Universidade Federal de São Carlos, 2023)
This research focuses on e-commerce shipment deliveries, specifically at the middle mile stage of the physical distribution process, with the objective of evaluating load unitizer options at the intermediate mile stage of e-commerce merchandise deliveries, considering factors conditions for your choice. Through a case study of a company in the sector, questionnaires were applied and interviews were conducted with a sample of employees to understand their perceptions and identify the most appropriate typology for this stage, with quantitative and qualitative analyzes being carried out. The results revealed three parameters that influence the choice of a unitizer: sustainability, which is related to the environmental impact of the material; product, which emphasizes the individual characteristics of the object; and process, which concerns the adequacy of the unitizer to the particularities of the intermediate mile. For the case studied, the unitizing device that proved to be the most appropriate was the modular plastic box. The choice of this unitizer was motivated by balancing the sustainability parameters and the product's characteristics, supported by the positive evaluations of those involved in the study. The main contribution of this work is to provide fundamentals for choosing a unitizer, helping organizations to understand the evaluated parameters and to select the best option to optimize deliveries in this logistical stage.
E-commerce shipments: conditioning factors for determining unitizers in the middle mile
Keywords: Unitizador; Comércio eletrônico; Unidades de agrupamento; Milha intermediaria.; Unitizer; e-commerce; Grouping unit; Middle mile; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO